Hubungan Asupan Zat Gizi Makro, Status Gizi dan Aktivitas Fisik Terhadap Tingkat Kebugaran pada Lansia di Kampung Jasugih Provinsi Banten - Ellawati, Evita Ella; Wahyuni, Yulia; Sapang, Mertien (Jurnal Nutrire Diaita (Ilmu Gizi), 2021)
AbstractBackground: The elderly are vulnerable to health problems and nutritional problems. One of the health problems that occur in the elderly can be in the form of a decrease in physical fitness cused by a reduced number of cell in the body. Aim: Analyzed the relationship between macro nutrient intake (energy, protein, fat, carbohydrate), nutritional status and physical activity on fitness level in the elderly in jasugih village, Banten province. Method: The study uses a quantitative approach with cross sectional design. The sample was taken   using purposive sampling technique with a total sample of 44 elderly as respondents. Bivariate analysis used Fisher’s exact test. Result: The age everage of the respondents in the Jasugih village Banten province is 65-80 years. Based on the results of the  Fisher exact test, it shows that there is a significant relationship between energy intake and fitness level (p-value = 0.037), there is no significant relationship between protein intake an fitness level (p-value = 0.554), there is a significant relationship between fat intake and fitness level (p-value = 0.033), there is a significant relationship between carbohydrate intake and fitness level (p-value = 0.034), there is no significant relationship between nutritional status and fitness level (p-value =  1.000), there is a significant relationship between physical activity and fitness level (p-value = 0.000). Conclusion: There is a significant relationship between energy intake and fitness level, there is no significant relationship between protein intake and fitness level, there is a significant relationship between fat intake and fitness level, there is  a significant relationship between carbohydrate intake and fitness level, there is no significant relationship between nutritional status and fitness level, there is a significant relationship between  physical activity and level.   Keyword: Elderly, Macro Nutrient Intake, Nutritional Status, Physical Activity   AbstrakLatar Belakang: Lansia sangat rentan terhadap masalah kesehatan maupun masalah gizi. Masalah kesehatan yang terjadi pada lansia salah satunya dapat berupa penurunan kebugaran jasmani yang disebabkan berkurangnya jumlah sel-sel yang ada di dalam tubuh. Tujuan: Menganalisis hubungan asupan zat gizi makro (energi, protein, lemak, karbohidrat), status gizi dan aktivitas fisik terhadap tingkat kebugaran pada lansia di kampung jasugih provinsi banten. Metode: Penelitian menggunakan pendekatan kuantitatif dengan desain Cross Sectional. Pengambilan sampel menggunakan teknik purposive sampling dengan total sampel sebanyak 44 lansia sebagai responden, analisis bivariat menggunakan uji statistik Fisher (Fisher Exact Test). Hasil: Rata-rata usia responden dikampung jasugih provinsi banten adalah 65-80 tahun. Berdasarkan hasil uji Fisher menunjukkan ada hubungan signifikan antara asupan energi dengan tingkat kebugaran (p-value = 0.037), tidak ada hubungan signifikan antara asupan protein dengan tingkat kebugaran (p-value = 0.554), ada hubungan signifikan antara asupan lemak dengan tingkat kebugaran (p-value = 0.033), ada hubungan signifikan antara asupan karbohidrat dengan tingkat kebugaran  (p-value = 0.034), tidak ada hubungan signifikan antara status gizi dan tingkat kebugaran (p-value = 1.000), ada hubungan signifikan antara aktivitas fisik dan tingkat kebugaran (p-value = 0.000). Kesimpulan: Ada hubungan signifikan antara asupan energi dengan tingkat kebugaran, tidak ada hubungan signifikan antara asupan protein dengan tingkat kebugaran, ada hubungan signifikan antara asupan lemak dengan tingkat kebugaran, ada hubungan signifikan antara asupan karbohidrat dengan tingkat kebugaran, tidak ada hubungan signifikan antara status gizi dengan tingkat kebugaran, ada hubungan signifikan antara aktivitas fisik dengan tingkat kebugaran.   Kata Kunci: Lansia, Asupan Zat Gizi Makro, Status Gizi, Aktivitas Fisik, Tingkat Kebugaran